The Optimum Production Management for Production Problems in Sadi Reservoir of Halfaya Oil Field - Hashim, Ameer H.; Al Jawad, Mohammed S.; Khlaty, Kassem A. (Journal of Petroleum Research and Studies, 2023)
Tight oil reservoirs suffer from a high decline in flow rates and instability of production rates, even after implementing the hydraulic fracturing technique to increase the production rate, but the problem still stands and needs to be overcome. This issue is found in the southeast of Iraq in the Halfaya oil field, especially in the Sadi formation. The goal of this study is to identify an optimum production rate for horizontal and vertical hydraulic fracturing wells using simulator software for prediction, in order to avoid highly depleted fracture storage capacity, which results from high production rates and depletion in flowing pressure. as well as to discuss the production behavior of the wells over their life cycles in the Sadi reservoir. In addition, we utilize a novel approach with production rates for horizontal hydraulic fracturing wells to reach a stable production rate. The results show that the production behavior of hydraulic fracturing wells is clear: producing at a high flow rate depletes the fluid potential of a fracture without providing a reservoir with an opportunity to compensate fluid into fracturing potential. In horizontal hydraulic fracturing wells, conducting an allowable flow rate that satisfied stability. We conclude a suitable flow rate has been identified to avoid high depletion rates and the plateau rate was different than that detected by the operator company, and we advise on future hydraulic fracture well development.